A clinical study of hemodynamically significant arrhythmias and QTc interval associated with thrombolysed and non thrombolysed acute myocardial infarction patients - Mohanani, Laxmi; Deopujari, Kuldeep; Singh Meena, Rangvendra; Dubey, T. N. (International Journal of Advances in Medicine, 2019)
Background: Arrhythmias are a common occurrence in acute myocardial infarction. Objectives of this study the hemodynamically significant arrhythmias and QTc interval in thrombolysed and non thrombolysed acute myocardial infarction patients. Methods: Two hundred patients of AMI were enrolled. ECG and cardiac parameters were examined. Arrhythmias and its various parameters like its incidence, type, frequency associated with site of infarction were recorded in thrombolysed and non thrombolysed patients of AMI. Results: AMI was more prevalent in the males (63.3%) and those with 41-50 years of age. Hypertension (35.7%), smoking (34.2%), and diabetes (23.1%) were the major risk factor. Incidence of AWMI (30.7%) is higher than IWMI (25.1%). Out of 200 subjects 130 were thrombolysed. Arrhythmias was observed in total 164 patients while 36 patients has no documentation of arrhythmias. Mean QTc was prolonged (546.88ms vs 404.33ms) in patients documented with arrhythmia compared with those who has no arrhythmia. Out of all arrhythmias, ventricular tachycardia was seen in 38% cases with 50% mortality and preponderance to antero lateral MI. Sinus Tachycardia was seen in 22% of cases with preponderance to Antero Lateral MI and persistence of Sinus Tachycardia was a prognostic sign, mortality being 12%. Complete Heart Block were seen with IWMI, incidence being 26%. Bundle Branch Block was common in AWMI (31%) than IWMI (10%). Conclusion: Tachyarrhythmias are common with AWMI and bradyarrhythmia’s in IWMI. Reperfusion arrhythmias are a benign phenomenon and good indicator of successful reperfusion.